Assessing the Effect of Partial Replacement of Fine Aggregates in Concrete with Iron Ore Tailings in Kigezi Sub-Region. - Musasizi, Allan (Kabale University, 2024)
This study aimed to assess the strength properties of concrete produced using IOT as partial replacement of the natural sand as fine aggregates. IOT is a waste product of iron ore mineral that is abundantly available in some regions and has the potential to be used as a sustainable alternative to traditional fine aggregates. In this research, the mixture, C15, was designed with 10%,25%, and 50% of IOT, natural fine aggregates and natural coarse aggregates. Properties considered included: workability, unit weight and compressive strength. Test results indicated that in all cases, IOT concrete gave high compressive strength than the conventional concrete. In conclusion, this study suggests that IOT can be used as a viable alternative to partially replace traditional fine aggregates in the production of concrete with acceptable strength properties for structural applications in pavement and floor slabs. Further research should however be carried out to investigate the durability and performance of IOT-based concrete.